2023
DOI: 10.3892/etm.2023.11914
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of supraorbital keyhole approach and extended transsphenoidal approach in endoscopic surgery for tuberculum sellae meningioma: A case series

Abstract: The endoscope-assisted supraorbital keyhole approach and extended transsphenoidal approach have been widely used in the treatment of tuberculum sellae meningiomas (TSMs). The purpose of the present study was to retrospectively analyze and compare the characteristics and efficacy of the two surgical approaches under the endoscope in the resection of TSMs. In the present study, 36 patients with TSMs who underwent surgical resection are presented, including one group of 17 cases with an endoscopic supraorbital ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Several studies have reported on the extent of tumor resection, visual outcomes, and complication rates associated with each approach. However, the absence of a recent systematic review and meta-analysis hinders the synthesis of these findings into a comprehensive understanding of the relative merits of MTAs and EEAs for TSMs [1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have reported on the extent of tumor resection, visual outcomes, and complication rates associated with each approach. However, the absence of a recent systematic review and meta-analysis hinders the synthesis of these findings into a comprehensive understanding of the relative merits of MTAs and EEAs for TSMs [1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…meta-analysis [9,10,12,[15][16][17]22]. The recurrence rate in the EEA group was 6/86 (6.9%), and it was 7/137 (5.1%) in the MTA group.…”
mentioning
confidence: 97%
See 3 more Smart Citations